Foundations of GTK+ Development - Krause, Andrew (Apress, 2012)
One of the most important aspects of an application is the interface that is provided to interact with the user. With the unprecedented popularity of computers in society today, people have come to expect those user interfaces to be graphical, and the question of which graphical toolkit to use quickly arises for any developer. For many, the cross-platform, featurerich GTK+ library is the obvious choice. Learning GTK+ can be a daunting task, because many features lack documentation, and even more are difficult to understand from only the API documentation. Foundations of GTK+ Development aims to decrease the learning curve and set you on your way to creating crossplatform graphical user interfaces for your applications. Each chapter in this book contains multiple examples that will help you further your understanding. In addition to these examples, the final chapter of this book provides five complete applications that incorporate topics from the previous chapters. These applications will show you how to bring together what you have learned to accomplish various projects. The beginning of each chapter provides an overview of what that chapter will cover, so that you are able to skip around if you want. Most chapters also contain exercises to test your understanding of the material. I recommend that you complete all of the exercises before continuing, because the best way to learn GTK+ is to use it.Ï #